Hematological Parameters Comparison in Systemic Lupus Erythematosus Patients With and Without Nephritis - Alya Marsya Sabrina; Edhyana Sahiratmadja; Laniyati Hamijoyo (Indonesian Journal of Rheumatology, 2026)
Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disorder commonly complicated by hematological disorders and lupus nephritis (LN). Kidney impairment and chronic inflammation may affect erythropoiesis and red blood cell parameters. However, there is limited information on the short-term changes of hematological parameters in patients with and without LN. This study aimed to compare the short-term changes of hematological parameters between two clinical visits in patients with SLE with and without LN. Methods: This retrospective observational study used data from the Hasan Sadikin Lupus Registry in 2023. A total of 202 female patients with SLE aged 18 years and older with complete hematological data from two clinical visits were included. Hematological parameters included hemoglobin, hematocrit, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), and red cell distribution width coefficient of variation (RDW-CV). Comparison of changes in parameters between the first and second visits was done separately for patients with and without LN using the Wilcoxon Signed Rank Test. Results: In patients with LN, there was a statistically significant reduction in MCHC between the first and second visits, whereas there were no significant changes in hemoglobin, hematocrit, MCV, MCH, and RDW-CV. In patients without LN, small but statistically significant changes were noted in hemoglobin, MCV, and MCHC. The degree of change was small and remained within the normal range. Conclusion: The short-term hematological parameters in patients with SLE are generally stable between two clinical visits. Only MCHC showed a significant change in patients with LN, indicating a selective and subtle hematological change rather than a global effect of LN. These results indicate a cautious interpretation of the short-term hematological changes and suggest that MCHC may be used as an auxiliary parameter for hematological assessment in patients with SLE and LN.